Who infuences family tourism decisions? Incorporating children’s perceptions - Rojas-de-Gracia, María Mercedes (Springer Nature, 2025)
This article continues the work of Rojas-de-Gracia et al. (2019) in which they question the appropriateness of relying on a single partner, male or female, to identify the decision-maker in tourism decisions. That study concluded that there is no general consensus among the members of the couple. As a solution, they proposed including the child as an impartial observer. This research tests that suggestion and shows that children’s perceptions difer from those of their parents, considering tourism decisions mostly autonomous and mainly dominated by the mother, contrary to parents’ perceptions of joint decision making. The practical implications of this fnding are discussed.
Keywords: Percepción social en niños; Pareja; Familia; Consensus; Children’s perception; Perceived infuence; Family decision making; Vacations; Couple roles